Jakość pracy naukowej, jej potwierdzenie a recenzja partnerska. Odbiór w środowisku naukowym i nieporozumienia. Postawy wobec recenzji partnerskiej (przekł. Tomasz Olszewski) - Mulligan, Adrian (Biblioteka, 2009)
Barnes J., Proof and the syllogism, w:Aristotle on Science: The „Posterior Analytics”,red. E. Berti, 1981. Lerner E., Fraud shows peer-review flaw, „The Industrialist Physicist” 8(6), 2003. Mulligan Adrian (Elsevier), Quality, certification and peer review, Information Services and Use, 28 (2008). Olson C.M., Peer review of the biomedical literature, „American Journal of Emergency Medicine” 8(4), 1990. Ziman J.M., Public Knowledge: An Essay Concerning the Social Development of Science, London 1968. Zuckerman H., Merton R.K., Patterns of evaluation in science: institutionalization, structure and functions of the referee system, „Minerva” 9(1), 1971.